FUNGITOXICITY OF WEED EXTRACTS TO TOMATO WILT PATHOGEN (FUSARIUM OXYSPORUM F. SP. LYCOPERSICI) - Qasem, J.R. . (Emirates Journal of Food and Agriculture, 2017)
Please see the scanned pdf version in full text